Executive Committee Minutes 2015-01-22 - Academic Senate:::::::::
Agenda approved. Minutes of 12/4/14 approved. Chair Report. President Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Ex Com rep on SEC Report. Faculty Eligible for Emeritus Status approved for Senate consent calendar. Co-Curricular Transcripts discussion. Academic Sustainability Plan for 2015 – 2016 discussion. Appointments/Elections for Search Committees – faculty approved for VP of Development Search. Review of alternative process for Senate meetings discussion. Senate Agenda approved.